مستوى القدرات البصرية الإدراكية لدى تلاميذ السنة الأولى ابتدائي - بنين, إبتسام; بنين, آمال; لعيس, إسماعيل (جامعة الوادي - University of Eloued, 2023)
ملخص: هدفت الدراسة الحالية إلى معرفة مستوى المهارات البصرية الإدراكية لدى التلاميذ المتمدرسين بالسنة الأولى ابتدائي، حيث استخدمنا المنهج الوصفي، ولتحقيق هذا الغرض عمدنا إلى تطبيق مقياس نبسي للأشكال الهندسية على عينة مكونة من (86) تلميذا وتلميذة متمدرسين بالسنة الأولى ابتدائي بابتدائية انصيرة الهاشمي بالوادي. فأظهرت نتائج الدراسة أن المهارات البصرية الادراكية كانت متوسطة عموما. Abstract: The present study aimed to know the level of visual perceptual skills of the first year of primary school pupils, where we used the descriptive approach. To achieve this objective, we applied the Nabsi (2) scale of geometric shapes on a sample of (86) male and female pupils studying in the first year of primary school at Ansira Al Hashimi in ElOued. The results of the study showed that visual perception abilities were generally average.
مقال
Keywords: الادراك ; المهارات البصرية الادراكية ; التعليم الابتدائي; Perception - perceptual visual skills; primary education